THE MESSAGES OF HUMAN CREATION AND UNIVERSE PERSPECTIVE OF QUR'AN AND HADITH - muhajir, ahmad (LTN NU Sulawesi Tengah, 2023)
Humans as one of the creations of Allah Subhanahu Wata'ala, have an important role in the existence of life on this earth. Nature is a sign of Allah, as evidence of the existence of the Supreme Creator, and also as a source of knowledge about the wisdom of Allah. The development of faith in religion and the advancement of science and technology should not be in opposition to each other. This research is a literature analysis that uses qualitative descriptive data to explore Educational Values in the Context of Human Creation and the Universe according to the views of the Quran and Hadith. The sources of the research come from various references such as books, journals, and other sources that discuss this theme. humans were first created from the ground and did not undergo an evolutionary process in the sense of change from primate forms. Allah SWT did not just create humans, but also provided a place for them to live and reproduce. It is undeniable that religion mandates every Muslim, regardless of gender, age, or position, to pursue knowledge as taught in the Quran and hadith. In the Quran and hadith, three types of human creation are described. First, the creation of Adam (peace be upon him). Second, the creation of Eve, and third, the creation of Adam's descendants. God created the entire universe, including the heavens, the earth and everything in it, in six periods of time. Every religion in the world encourages its adherents to seek and develop knowledge, including Islam.